The impact of student heterogeneity in implementation of Activity Based Oral English - Rohan, R.M.D. (My University, 2012)
The Kannangara report in 1943 which suggested to make vernacular languages the medium of instruction, introduced a new subject to Sri lankan education system i.e. English as a second language. Since the introduction, it started to be one of the subjects that attracted the attention of education researchers. Still, there is a problem about the age level at which English should be introduced as a second language. Throughout the history of Sri lankan education after the independence, English has been tried to be introduced at different levels. The most recent attempt is introducing communicative English in ABOE as a part of Environment Related Activities in grade 1. It is an accepted fact that from grade 1, students begin to show their individual differences and begin to build up as independent personalities acquiring their culture. These individual differences are referred to as student heterogeneity and it is concerned in the research with ABOE. The research pays its attention on how the teachers can make use of ABOE to minimize the student heterogeneity and its effects on learning teaching process. The research is based on the following objectives; 1. Explain the concept of student heterogeneity. 2. Identify the theoretical basis of Activity Based Oral English. 3. Examine how ABOE is being implemented in the classroom. 4. Analyze how the problem of student heterogeneity is addressed in relation to how Activity Based Oral English is practiced. 5. Suggest ways of minimizing student heterogeneity through ABOE. Theoretical foundation of ABOE and student heterogeneity were identified the review of literature in chapter 2. To achieve the above mentioned objectives the research was conducted with the help of the following instruments. 1. A questionnaire to 100 teachers of grade 1 and 2 classes. 2. Observation of 15 era lessons in three schools. 3. Informal interviews/discussions. The questionnaire and the observation schedule were designed so that the objectives are achieved. They were tested in advance and necessary adjustments were made. Fifteen ERA lessons were observed going by the observation schedule. Simultaneously, data was gathered through informal discussions and interviews. Then the questionnaire was administered among 125 teachers. The results of 100 answered questionnaires were analyzed and discussed in relation to the data gathered through observation and informal interviews. Through the analysis the following findings were made. ABOE as a new subject area some teachers think it to be an extra burden whereas some feel it as an interesting way of introducing English subject to the students. Anyway it was understood that the students practice it to different levels in the classroom. In practicing ABOE teachers’ knowledge of English knowledge appeared to affect the quality of teaching. It was further revealed that majority of the teachers did not have a clear understanding about what ABOE is. In relation to teacher training of ABOE several problems were revealed. A major problem found in relation to teacher training was that those programmes did not have uniformity in the duration at different areas where the research was conducted. It was further revealed that although these programmes provided the teachers with some kind of knowledge it was not what they expected. Instead, they wanted practical solutions to the problems they face in the classroom. When student heterogeneity is considered it was revealed that some teachers do not accept student heterogeneity to be the natural situation of the classroom. Some of the teachers who accept that it is the natural situation do not perceive it to be a problem. Those who identify student heterogeneity to be a problem do not have any idea about the techniques to handle it effectively in the classroom or how to minimize it using new techniques. Although the teachers say that they use different techniques to handle student heterogeneity, observations of the lessons proved that they just followed routine classroom activities. Some teachers tried to solve the above problem by dividing the students into equal ability groups whereas majority of them divided the students into mixed ability groups. As solutions to the above problems, following recommendations were made. Suggesting a flexible list of words to be introduced during the lessons would help the teachers to adapt easily to the new situation. To compensate the lack of knowledge of English of the primary teachers, the work of ISAs is suggested to extend to the ABOE also. If it is not possible a new set of mentors for ABOE can be appointed. There should be an experienced body of officials to regulate the teacher training programmes. Teacher training should be revised to meet the demands of the teachers. To minimize the student heterogeneity in the class three types of activities are suggested. They are whole class activities, group activities and pair activities. Whole class activities are further divided into two sub parts as; Start-up activities that are followed by group work and Whole class activities performed at different levels. They are further described in chapter five.